Similes In Novel Looking For Alaska By John Green - Antary Octha Sri Devi, Ni Putu; Budiasa, I Gede; Shanti Sari Dewi, A. A. Sagung (Humanis, 2018)
The paper entitled “Similes in Novel Looking for Alaska by John Green” focuses on the kinds of simile and the meaning of simile found in the novel. The data was collected by reading the novel intensively, giving underline and taking note the similes found in the novel. The collected data was analyzed using qualitative method based on theory of figurative language, particularly simile. The main theory used in the analysis of the kinds of simile is proposed by Zhang Xiu Guo in a book entitled English Rhetoric (2005) and the analysis of type of meanings uses theory proposed by Leech (1981) in his book entitled Semantics. From the analysis of the data, there were two types of similes found, namely simile in terms of function and structure. Functionally there were three kinds of simile found, they are descriptive, illuminative, and illustrative similes, meanwhile structurally two kinds of similes were identified, they are closed and open similes. The meanings of similes found are connotative and conceptual meanings.